Efektivitas Teknik Rebozo Menggunakan Kazo terhadap Penurunan Intensitas Nyeri dan Percepatan Kemajuan Persalinan - Ayudarista, Lastriati Dewi; Sutisna, Ma’mun; Nurlatifah, Teni; Deborah, Anita; Sabarudin, Udin; Wijayanegara, Hidayat (Poltekkes Kemenkes Bandung, 2026)
Background: Prolonged labor occurs due to prolonged labor pain, where the mother feels unable to endure the pain, leading to premature pushing before the cervix reaches full dilation. This condition posed a risk of cervical swelling and labor dystocia. The rebozo technique was a non-pharmacological method used to help manage pain during labor without medication. Objective: This study aimed to analyze the effect of the rebozo technique using kazo cloth on pain intensity and labor progress at Zhafira Zarifa Clinic, Karawang Regency. Methods: This study employed a quasi-experimental design with a pretest–posttest two-group design approach. The study sample consisted of 60 multigravida mothers in the active phase of the first stage of labor, selected using accidental sampling. Inclusion criteria: multigravida mothers in labor, active phase cervical dilation of 4-7 cm, single fetus with occiput posterior presentation, uncomplicated pregnancy, and normal fetal heart rate. The experimental group (30 participants) received the rebozo technique using kazo, while the control group (30 participants) practiced breathing relaxation techniques. Pain intensity was measured using the Numerical Rating Scale (NRS), with a pain range of 7–10 as the sample criteria. Data analysis was conducted using the paired t-test in SPSS. Results: The study found a significant effect of the rebozo technique using kazo on reducing pain intensity and accelerating labor progress, with a p<0.001. Conclusion: This technique was proven effective in reducing pain and expediting labor. It was expected that this method could serve as an alternative for non-pharmacological pain management during labor.